Appalachian Curriculum 1995 - Gibson, Lisa (Appalachian State University, 1995)
An Appalachian Curriculum is the product of a week-long teacher workshop held on the campus of Appalachian State University in June, 1995. The purpose of the workshop was to allow children of the Southern Appalachian region to gain better educational access to the tremendous resources of this area.